Characteristics of Beef Cattle Farmers at Southern West Java - Dede Kardaya; Ristika Handarini; Wini Nahraeni; Elis Dihansih; Deden Sudrajat (Indonesian Journal of Applied Research (IJAR), 2020)
The study aimed to identify characteristics of beef cattle farmers along the street corridor of Southern West Java. The study used a survey method in which purposive sampling technique was applied to collect data from 13 sub-districts of five districts along the street corridor of Southern West Java. Result of the study showed that eight categories of cattle farmers with their respective characteristics, namely: 1) the age of farmers, in the productive category (91%); 2) the level of education, mostly at the level of elementary school education (62%); 3) farming experience, most experience for 11-20 years (30%); 4) the nature of livestock business, is a side business (70.8%); 5) number of family dependents, with the highest number of three family dependents (32%); 6) livestock ownership, is their-self owned (67%); 7) cattle origin, with own purchases namely 46%, and 8) business scale, with many livestock owned by 1-3 beef or 50%.